SVM based hysteresis current controller for a three phase active power filter - Leow, Pei Ling; Ahmad Azli, Naziha (IEEE, 2004)
A space vector modulation (SVM) based hysteresis current controller (HCC) technique for a three phase shunt active power filter is proposed. The switching control algorithms of the proposed SVM based HCC manage to generate compensated current according to the reference current harmonics extraction is based on the instantaneous active and reactive power theorem in time domain by calculating the power compensation. A closed loop control system is implemented and the error current is the difference between the reference current obtained from the power compensation and the actual current that needs to be injected back into the line. By implementing this control strategy, the active power filter (APF) manages to generate better compensated harmonics currents to the line.